Analisis Faktor Tingkat Pendidikan di Jawa Tengah Tahun 2021 - Maziyah Mufidah Wahyudiono; Puspa Damai Kukuh Hati; Sri Pingit Wulandari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Nation-building requires long-term investment focused on improving human resource (HR) quality, where higher education levels play a crucial role in shaping superior HR. In Indonesia, the government continuously strives to expand access to and improve the quality of education across regions, including in Central Java Province. However, disparities in educational attainment remain a challenge, influenced primarily by social, economic, and demographic factors. This study aims to analyze the factors affecting education levels in Central Java in 2021, a post-pandemic year, using the Principal Component Analysis (PCA) approach. Suspected influential factors include poverty rates, gender ratios, population growth rates, gross enrollment rates, net enrollment rates, expected years of schooling, and average years of schooling. The analysis results show that the data characteristics of these factors indicate asymmetrical distributions and high variability, as observed from wide boxplots for most factors. Only the expected years of schooling exhibit lower variability, with the presence of outliers. Assumption tests reveal that the data follow a multivariate normal distribution, are sufficient for factor analysis, and are dependent. The principal component analysis results indicate that two components are sufficient to explain overall data variability. The factor analysis forms two new components, identified as the welfare and education factor and the education participation factor.